SIMULATION OF WATER EVAPORATION ON ULTIMONITORED THERMOMIX®: POTENTIAL APPROACH FOR STUDIES ON MILK EVAPORATION - Stephani, Rodrigo; Francisquini, Júlia d’Almeida; Paula, Igor Lima de; de Carvalho, Antônio Fernandes; Oliveira, Luiz Fernando Cappa de; Perrone, Ítalo Tuler (Revista do Instituto de Laticínios Cândido Tostes, 2017)
It was simulated the industrial evaporation process using a multi-monitored Thermomix®. To validate the hypothesis that this equipment could act as a laboratory- scale evaporator, we evaporated water from milk to produce dulce de leche. Using this equipment, we were able to precisely determine mass changes throughout the process, observe the effect of the exhaust system on the evaporation, obtain dulce de leche with market composition, and determine the effect of sugar addition on water evaporation. The error between the observed boiling point temperature and that predicted by theory was 2%; as a consequence, the equipment could be used to establish Dühring curves. It was found that the Thermomix® multi-monitored configuration was a simple and inexpensive equipment for simulate evaporation in industrial dulce de leche production.